2021
DOI: 10.1186/s12876-021-01921-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of complete omentectomy in patients with resectable gastric cancer: a meta‑analysis and systematic review

Abstract: Background We performed a meta-analysis to investigate the efficacy of complete omentectomy (CO) in patients undergoing radical gastrectomy for gastric cancer. Methods We conducted a literature search in PubMed, Web of Science, and the Cochrane Library databases for clinical research that compared CO with non-complete omentectomy (NCO). These articles were published prior to April 2021. Overall survival (OS) rates, relapse-free survival (RFS) rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Seven previous meta-analyses studied the oncologic feasibility of PO [ 326 327 328 329 330 ]. All the meta-analyses showed that PO was not inferior to TO regarding OS and relapse-free survival.…”
Section: Surgical Treatment ( Flowchart 3 ...mentioning
confidence: 99%
“…Seven previous meta-analyses studied the oncologic feasibility of PO [ 326 327 328 329 330 ]. All the meta-analyses showed that PO was not inferior to TO regarding OS and relapse-free survival.…”
Section: Surgical Treatment ( Flowchart 3 ...mentioning
confidence: 99%
“…It functions as a protective cushion and is responsible for peritoneal defenses. 1 Gastric cancer (GC) is the fourth most common cancer worldwide. In 2020, a total of 1,089,103 (5.6% of all cancer) new gastric cancer cases, causing 768,793 deaths (7.7% of all cancer), were estimated.…”
Section: Introductionmentioning
confidence: 99%
“…Being the most common recurrence in GC, peritoneal metastases are estimated to occur in approximately 55-60% AGC patients, thus being deemed a leading factor in GC poor outcomes [5]. Peritoneal recurrence is commonly detected in patients undergoing gastrectomy for cT3 and cT4 GC [6,7]. As concerns metastatic peritoneal sites, the greater omentum is the most common metastatic area in AGC.…”
Section: Introductionmentioning
confidence: 99%
“…Several mainly retrospective observational studies analyzed the role of complete omentectomy (CO) in addition to radical gastrectomy in GC patients [16][17][18][19][20][21]. Given the presence of significant bias in the aforementioned studies, different meta-analyses have been developed in order to improve the present evidence [6,7,14,[22][23][24][25][26]. Such meta-analyses demonstrated that gastrectomy without CO gives similar, even better short-and longterm results than gastrectomy with CO, although many of those studies also included populations with early gastric cancer (EGC) [6,7,14,[22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation